Efektivitas Pembelajaran Daring Berbasis YouTube Terhadap Kemampuan Pemecahan Masalah Matematika - Muhammad Syahril Harahap; Marzuki Ahmad; Sintiya Mayuni Lumbantobing (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2022)
The aim of this study is to describe the effectiveness of the application of YouTube-based online learning on the Mathematics Problem Solving Ability (MPSA) of students in class VIII-5 of SMP Negeri 4 Padangsidimpuan. This research uses descriptive quantitative method with a sample of 17 students. Data collection techniques in this study using observation and tests. Based on the results of descriptive analysis, it was found: (a) The average application of YouTube-based online learning was 3.56 with the